Adenylyl Cyclase (AC) Mediates the Antidepressant-Like Effects of Tropisetron on a Mouse Model of Maternal Separation Stress. (22nd April 2021) - Hosseinzadeh, Ali; Boroujeni, Shakiba Nasiri; Saghaei, Elham; Loriooini, Zahra; Dehkordi, Saeid Habibian; Balali-Dehkordi, Shima; Rahimi-Madiseh, Mohammad; Amini-Khoei, Hossein
Abstract : The adenylyl cyclase (AC) pathway is involved in the pathophysiology of depression. Finding new antidepressants with high medicinal properties and low side effects is warranted. Therefore, this study was designed to determine the antidepressant-like effect of tropisetron on a maternal separation (MS) model in mice, considering the possible role of AC. NMRI male mice were divided into eleven groups. The control group was treated with saline and MS groups were treated with saline, tropisetron (a 5-HT3 receptor antagonist) at doses of 1, 3, and 5 mg/kg; forskolin (an activator of AC) at doses of 5, 10, and 25 mg/kg; a subeffective dose of forskolin with a subeffective dose of tropisetron; and an effective dose of tropisetron plus an effective dose of NB001 (3 mg/kg) (an AC inhibitor). After treatment, animals were subjected to behavioral tests including the forced swimming test (FST), splash test, and open field test (OFT). We showed that MS caused depressive-like behaviors determined as an increase in the immobility time in the forced swimming test (FST) and decreased grooming time in the splash test. Our results showed that administration of tropisetron, as well as forskolin, mitigated the depressive-like behaviors in MS mice. We found that coadministration of a subeffective dose of tropisetron plus a subeffective dose of forskolin potentiated the antidepressant-like effect of tropisetron. However, coadministration of an effective dose of NB001 with an effective dose of tropisetron did not significantly affect the antidepressant-like effect of tropisetron. We concluded that the antidepressant-like effects of tropisetron on MS mice are partially mediated through the adenylyl cyclase pathway.